Crystal structure of the UBR‐box from UBR6/FBXO11 reveals domain swapping mediated by zinc binding. (25th July 2017) - Muñoz‐Escobar, Juliana; Kozlov, Guennadi; Gehring, Kalle
Abstract: The UBR‐box is a 70‐residue zinc finger domain present in the UBR family of E3 ubiquitin ligases that directly binds N‐terminal degradation signals in substrate proteins. UBR6, also called FBXO11, is an UBR‐box containing E3 ubiquitin ligase that does not bind N‐terminal signals. Here, we present the crystal structure of the UBR‐box domain from human UBR6. The dimeric crystal structure reveals a unique form of domain swapping mediated by zinc coordination, where three independent protein chains come together to regenerate the topology of the monomeric UBR‐box fold. Analysis of the structure suggests that the absence of N‐terminal residue binding arises from the lack of an amino acid binding pocket. Abstract : PDB Code(s):5VMD